VASCULAR ENDOTHELIAL GROWTH FACTORS IN HEART TRANSPLANT REJECTIONS - O. P. Shevchenko; E. A. Stakhanova; A. O. Shevchenko; N. P. Mogeiko; O. E. Gichkun (Вестник трансплантологии и искусственных органов)
Aim: to determine the clinical significance of vascular endothelial growth factors VEGF-A, VEGF-D, PlGF-1 to assess the risk of cardiovascular complications in heart recipients. Materials and methods. 103 patients, aged 16 to 73 years, 85 males and 18 females. 65 recipients (47 men and 18 women) had dilated cardiomyopathy, 38 – coronary heart disease (CHD). The concentration of VEGF-A, VEGF-D, PlGF-1 was measured using xMAP technology with sets of reagents Simplex ProcartaPlex™. Results. After HTx the level of VEGF-A significantly decreased, p = 0.001. There were no correlations between the levels of VEGF-A, VEGF-D and PlGF-1 with age, gender and diagnosis. After HTx VEGF-A level was higher in recipients with ACR than in those without it (p = 0.001). ACR frequency was significantly higher in patients with high VEGF-A level (≥316.5 pg/ml, RR = 5.8 ± 0.5, AUC = 0.779). After HTx PlGF-1 level was higher in recipients with ACR too (p = 0.039). ACR frequency was significantly higher in patients with high PlGF-1 level (≥5.33 pg/ml, RR = 1.8 ± 0.5, AUC = 0.65). There were no correlations between VEGF-D level with ACR and all three biomarkers with AMR. ACR frequency was significantly higher with both high VEGF-A and PlGF-1 levels (RR = 6.4). Conclusion. Serum levels of VEGF-A and PlGF-1 after HTx may be regarded as indicators of increased risk of ACR.